Henry Burnett and Roy Nitzberg, Composition, Chromaticism and the Developmental Process: A New Theory of Tonality (2007) - Wason, Robert (Journal of the Society for Musicology in Ireland, 2008)
A review of Henry Burnett and Roy Nitzberg, Composition, Chromaticism and the Developmental Process: A New Theory of Tonality (Aldershot: Ashgate, 2007), ISBN 978-0-7546-5162-8, xxvii + 402 pp, £55/99.95